RhoGDIα regulates spermatogenesis through Rac1/cofilin/F-actin signaling - Haixia Zhu; Zongzhuang Wen; Aizhen Zhang; Dongyue Liu; Hongxiang Wang; Yin Cheng; Xing Yang; Yu Xiao; Jianyuan Li; Daqing Sun; Bin Wu; Jiangang Gao (Communications Biology, 2023)
RhoGDIα knockout mice show low male fertility and compromised spermatogenesis, with an underlying defect in F-actin cytoskeleton depolymerisation, which can be alleviated by inhibiting Rac1.